Divorce Decision for Women: In Terms of Biopsychosocial - Devi Puspitasari; Jatie K. Pudjibudojo; Hartanti Hartanti (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2021)
The purpose of this study is to explain the divorce decision-making process in women in terms of a biopsychosocial approach. This study uses a qualitative case study method with in-depth interview techniques. Respondent is a 32-year-old woman who was divorced from her husband due to economic dishonesty and infidelity. The results showed that even though the decision to divorce was made on its own initiative and with a strong determination to file for divorce, it still had an impact on the biopsychosocial aspect. The dominance of the problem is in the social aspect which is has an impact on the biological and psychological aspects. Subject always think about the status of widows and also the response of the family who blamed the subject for the occurrence of divorce. By the social response to, it causes biological impacts including insomnia and decreased appetite, resulting in significant weight loss. Psychological aspects that arise are cognitive, affective, and behavioral symptoms. The coping stress used is self-control, positive and realistic thinking and using strategic planning, so that it will no longer sink in the future.